USULAN PERBAIKAN TATA LETAK AREA GUDANG PRODUKSI BAHAN BAKU VENEER MENGGUNAKAN METODE CRAFT DI CN VENEER - Muhammad Alan Nazid Solih; Gunawan Mohammad; Budi Lovian (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
This study aims to improve the warehouse layout of raw material production at CN Veneer, Jepara, through the application of the CRAFT (Computerized Relative Allocation of Facilities Technique) method. The current layout presents inefficiencies in terms of long material handling distances and limited maneuverability due to narrow aisles and disorganized material storage. By employing data collection methods such as observation, direct measurement, and interviews with warehouse staff, this research developed a layout model that minimizes total material handling costs (OMH). Using iterative simulations, the CRAFT method generated an optimized layout alternative that significantly reduces travel distance, handling time, and improves spatial efficiency. The final layout proposal shortens material routes, improves accessibility, and enhances operational effectiveness in the warehouse.